PERCEIVED USEFULNESS CAN MEDIATE THE INFLUENCE OF PERCEIVED EASE OF USE ON CUSTOMER DECISIONS IN USING BCA MOBILE - Violita, Chynthia Eka; Wenats, AG Eka; Utami, Eva Yuniarti; Putra, Johni Eka; Ariwibowo, Prasetio (JURNAL ILMIAH EDUNOMIKA, 2024)
AbstractThis research is a quantitative study with an explanatory approach. The data used in this article is primary data that researchers obtained from 500 BCA Bank customers spread throughout Indonesia with the criteria of being 22 to 40 years old which is the productive age to understand and use the BCA Mobile application effectively. The data used in this article was analyzed using the smart PLS 4.0 analysis tool. The result in this article show the Perceived Ease of Use variable can have a positive relationship direction and a significant influence on Customer Decisions. The first hypothesis can be proven because the P-Values are positive and below the significance level of 0.05, namely 0.006These results are because the Perceived Ease of Use can easily demand a customer to decide to use BCA mobile because it can make all the work and challenges they face easier. The next hypothesis, namely the perception of usefulness, can strengthen the influence of the Perceived Ease of Use on Customer Decisions, can also be proven because the same thing, namely the P-Values are below the significance level of 0.05, namely 0.000, more significant than direct testing, namely 0.006. This is because a customer can happily do anything that will benefit him, both morally and materially, including deciding to use BCA mobile Keywords: Investment, Econmic Growth, Exports